Assessment of Parking Facilities in Public Areas: The Case of Keffi Town - Olatunji, Ayodeji Solomon; John, Enogela Ahmed; Adedeji, Adeyemi Adewumi; Mikaila, Muhammed Loko (UI Scholars Hub, 2024)
The absence of adequate parking facilities in residential and public areas remains a significant issue in developing countries, often disrupting economic activities and environmental quality. In Keffi town, the increasing demand for parking exceeds the available supply, leading to congestion and inefficiency. This study evaluates the current public parking facilities, focusing on provision levels, infrastructure conditions, and management frameworks. Primary data were gathered using structured questionnaires and direct observations, with 328 valid responses analyzed through descriptive statistics. Results indicate that prolonged vehicle stays exacerbate congestion, such as at Nasarawa State University (32.8%) and Federal Medical Centre (29.1%). Parallel parking dominates (65.2%), and 91.6% of users rely on traditional search methods, highlighting the absence of modern parking guidance systems. The study recommends improving parking infrastructure with an emphasis on environmental standards, user convenience, safety, and the enforcement of effective regulatory frameworks.